2020
DOI: 10.1007/s40753-020-00121-w
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Collaborative Exams have Little Impact on Subsequent Exam Performance in Undergraduate Mathematics

Abstract: In this paper, I investigate whether two-stage exams aid learning in undergraduate mathematics, as measured by students’ performance on subsequent exams. In a two-stage exam, students complete the exam individually then form into groups to solve it again, with grades based on a combination of the two stages. Previous research in other disciplines has found mixed results about their effect on subsequent performance, and little is known about their use in undergraduate mathematics. Here, I report on three studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In this study, where all students in a group got a particular question wrong, the group collectively got that question right in the group stage 57% of the time. A similar study by Kinnear (2021) found this occurred 17% and 29% of the time in two different settings. These results highlight the power of collaboration to correct misconceptions.…”
Section: Increase Of Group Marks Over Individualmentioning
confidence: 62%
See 1 more Smart Citation
“…In this study, where all students in a group got a particular question wrong, the group collectively got that question right in the group stage 57% of the time. A similar study by Kinnear (2021) found this occurred 17% and 29% of the time in two different settings. These results highlight the power of collaboration to correct misconceptions.…”
Section: Increase Of Group Marks Over Individualmentioning
confidence: 62%
“…3) Questions should be multiple-choice rather than written answers. There is evidence to suggest that students engage in complex discussions around answers for even multiplechoice questions in two-stage examinations (Kinnear, 2021;. Marking of multiple-choice type assessments is also well-suited to large classes; the majority of large-cohort studies surveyed here used this type (e.g., Eaton, 2009;Fournier, Couret, Ramsay, & Caulkins, 2017;McCurdy, Volterman, Shiell, Zeadin, & Dunn, 2017;Yuretich, Khan, Leckie, & Clement, 2001).…”
Section: Employing Two-stage Examinations In Large Undergraduate Coursesmentioning
confidence: 99%
“…Importantly, group exams have the potential to assess social competencies needed in the professional workplace (Jang, 2016) and send students the message that collaboration is a valued central practice of doing science and engineering (Boud, 1990;Gilley & Clarkston, 2014;James, 2014;Rieger & Heiner, 2014). However, while two-stage exams appear to improve motivation and lower stress, there are mixed reports about whether they actually improve learning (Gilley & Clarkston, 2014;Kinnear, 2020;Leight et al, 2012).…”
Section: Two-stage Examsmentioning
confidence: 99%
“…Several studies have shown that student scores improve significantly on the group exam, for instance in veterinary physiology (9), nursing education (10), general medical education (11) and exercise physiology (12). While some studies find long-term learning benefits (10,13), others find that there is little evidence that the improved learning is maintained by students to the end of the course (e.g., 14,15). Our use of two-stage exams was not primarily chosen to increase long-term student performance (although that would of course be a benefit), but to create a clear course objective of community and collaboration among our students.…”
Section: Introductionmentioning
confidence: 99%